Autoantibodies in Sjögren's syndrome and its classification criteria - Veenbergen, Sharon; Kozmar, Ana; van Daele, Paul L.A.; Schreurs, Marco W.J. (Journal of translational autoimmunity (Online), 2022)
Sjögren's syndrome (SS) is a systemic autoimmune disease characterized by immune-mediated injury of exocrine glands. Extensive lymphocytic infiltrates may contribute to the destruction and loss of secretory function of glands. B-cell hyperactivity is a key feature of the disease resulting in the production of a diverse array of autoantibodies in these patients. Although not specific for SS, anti-Ro/SSA and anti-La/SSB antibodies have been useful biomarkers for disease classification and diagnosis. During recent years, novel autoantibodies have been discovered in SS. In this review, we summarize the historical role and clinical relevance that autoantibodies have played in the classification criteria of Sjögren's syndrome, discuss laboratory aspects in antibody detection and review the role of novel autoantibodies in predicting particular stages of the disease, clinical phenotypes and long-term complications. •Different classification criteria for SS have been developed over time with remarkable changes in the serological item.•Challenges in the harmonization of autoimmune diagnostics involve the heterogeneity in autoantibodies and diagnostic methods.•The difficulties in standardization and harmonization in autoimmune diagnostics may have an impact on disease criteria.•Particular disease stages, clinical phenotypes and long-term complications may be associated with specific autoantibodies.